Leadership 4.0: How Transformational Leadership Shapes Employee Engagement in the Era of Industry 5.0 - Elok Cahyaning Pratiwi; Fajar Purwanto; Mochamad Irfan (Jurnal Informatika Ekonomi Bisnis, 2025)
In the era of Industry 5.0, where human-centric innovation and advanced technologies intersect, leadership plays a critical role in shaping sustainable employee engagement. This study explores how transformational leadership—through its core dimensions of inspirational motivation, individualized consideration, intellectual stimulation, and idealized influence—drives engagement in digitally augmented work environments. Using a qualitative research design, data were collected through semi-structured interviews with 15 professionals across technology-intensive organizations. Thematic analysis revealed that transformational leaders foster emotional resonance, developmental support, and cognitive challenge, which are essential for engagement in hybrid and AI-integrated workplaces. Additionally, the digital context emerged as a moderating layer that influences the effectiveness of leadership behaviors. The findings suggest that Leadership 4.0, when grounded in transformational principles, serves as a strategic enabler for building trust, innovation, and resilience among employees. This study contributes to leadership theory in the context of Industry 5.0 and provides practical insights for organizations seeking to enhance workforce engagement through empathetic and adaptive leadership.